Effect of stiffeners in lateral stiffness of masonry infill reinforced concrete (RC) frames - Kawan, Chandra Kiran (Journal of Science and Engineering, 2015)
Infilled frames are reinforced concrete frames with masonry infill. The provision of masonry walls as infill increases the lateral stiffness of frame. Unreinforced masonry infill effects the strength and stiffness of frame but being ignored for a long time. The main objective of this paper is to study the individual and combined effect of infill masonry wall, stiffeners and wooden frame in the lateral stiffness of infill reinforced concrete frame with central opening, with and without gap element consideration. From the analysis using SAP software, it is observed that with increase in openings, stiffness decreases but introducing stiffeners and wooden frame increases the lateral stiffness. Embedding the gap element as the boundary condition reduces the stiffness of the infilled frame. Numerical investigations are carried out by finite element modeling for analyzing the behavior of infilled frame. The single equivalent diagonal strut width was determined by obtaining the same lateral stiffness from finite element model, and also strut reduction factor for different conditions with central openings are proposed.